KAJIAN STRATEGI ZAKAT, INFAQ DAN SHADAQAH DALAM PEMBERDAYAAN UMAT - Abdul Haris Nasution; Khoirun Nisa; Muhammad Zakariah; Muhammad Askari Zakariah (Jurnal Ekonomi Bisnis Syariah, 2018)
The objective of this paper was to determined action plan of zakat, infaq and shodaqah (ZIS) to empowerment of ummah. Management of starategy on collection, analyze (data of mustahiq), and distribution should be reformulated. To empowerment of ummah, ZIS should be have character based on sosial, economic, and ecology. Model of management (collected, analyze, and distribution) should be constructed by SWOT analysis, before it is done. Finally, management of ZIS should be change on focus distribution model in the productive form of a creative, ZIS is realized in the form of capital either for the construction of social projects or increase the capital of small business enterprises.